Multiple verrucous lesions of the feet in Waldenström macroglobulinaemia. (21st October 2017) - Naito, R.; Koga, K.; Masaki, M.; Fujii, N.; Ito, K.; Koga, M.; Imafuku, S.
Abstract : Clickhere for the corresponding questions to this CME article.